The Italian straw hat = Un chapeau de paille d'Italie - Labiche, Eugène 1815-1888; Michel, Marc 1812-1868 (Flicker Alley, 2010)
A bridegroom is riding to his marriage when his horse eats a straw hat hanging on a branch while its owner, a married lady, enjoys a tryst behind the bush with her lover, a fierce hussar. She cannot go home without her hat, so the groom interlaces his wedding with an attempt to find madam a twin chapeau, launching a series of misunderstandings and embarrassments. [Flicker Alley]
Bildformat 1.33:1
Orig.: Frankreich, Deutschland 1928
Enth. "La Tour" ; "Noce en Goguette" ; enclosed booklet ; "Un chapeau de paille d’ Italie" by Eugene Labiche and Marc Michel, here in an English translation of 1916 as "The leghorn hat" as a DVD-ROM extra